Art Education in the Secondary Schools of Southern India A Study - C.S., Anupama; N.C., Kiran Babu (JOURNAL OF INDIAN EDUCATION, 2020)
The present paper has attempted to provide a review of issues concerning the art education in the Secondary Schools of Southern India. The data were collected from Head teachers and Art education teachers of selected state run government schools and KVs from South Indian states. It has presented concerns and the essence of methods of art education and raised issues about the trends, assessment and intervention approaches towards art education. The study reveals that most of the state run schools the art education as an school subject is in a neglected stage while in KVs due importance could be seen. The teacher recruitment in government school has been another important issue revealed through the study. Study also highlights that most of the art teachers uses strategies like drawing and sketching and demonstration in their classroom transaction.